EDUKASI DIGITAL MARKETING PADA PELAKU UMKM AGROWISATA PALOH NAGA DALAM PERSPEKTIF EKONOMI ISLAM - Adik Tya Hasibuan; Ika Damai Sari; M. UKi Sofyanda; Wahyu Syarvina (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity aims to enhance the competitiveness of Paloh Naga Agrotourism MSMEs and restore visitor numbers after the fire, by using digital marketing strategies within the perspective of Islamic Economics. The method utilized is descriptive qualitative with a participatory approach, delivered through seminars, training, and mentoring for MSME actors and the people of Denai Lama Village. The results indicate an increase in participants' knowledge and skills in managing business accounts and creating engaging promotional content. The application of digital marketing via social media, emphasizing the principles of honesty, justice, and trustworthiness (avoiding gharar and tadlis), proved effective in expanding the market and improving the halal image of the MSMEs. In conclusion, the program successfully supports the economic transformation of the Paloh Naga community towards becoming more independent, innovative, and just, in accordance with sharia principles.